NLRP3 Inflammasome — a new universal target of asymptomatic hyperuricemia and gout management - P. A. Lebedev; L. T. Volova; N. K. Osina; E. V. Paranina (Рациональная фармакотерапия в кардиологии, 2024)
From modern perspective, hyperuricemia should be considered as a trigger of inflammatory activity in tissues and organs, leading to the formation of tophi, arthropathy, kidneys and cardiovascular system damage. Similarly, hypercholesterolemia, a proven factor in atherogenesis-far from all patients leads to the development of relevant clinical events. This commonality may be explained by the involvement of universal inflammatory mechanism. The key mediator of gout attacks is recognized as IL-1β, a product of NLRP3 (NLR family pyrin domain containing 3) inflammasome activation (complex multiprotein), responsible for local inflammatory response in synovial membrane and periarticular tissues with participation of macrophages and neutrophils. NLRP3 inflammasome activation is carried out by uric acid crystals, cholesterol exclusively after priming by lipopolysaccharides, peroxidation products and other damage factors associated with aging and comorbid conditions typical for gout and cardiovascular diseases. In addition, NLRP3 inflammasome activity is genetically determined and determines the frequency of these conditions. The discussed mechanism explains why the impact on factors associated with comorbidity is able to reduce the frequency of gout attacks along with cardiovascular outcomes. New clinically relevant pleotorpic effects of statins, sodium-glucose cotransporter-2 inhibitors, which have advantages over urates-lowering therapy in patients with asymptomatic hyperuricemia and can modify the course of gout, are demonstrated. Their anti-inflammatory properties, cardio and renoprotective effects, and tolerability advantages are emphasized. Blocking the activity of inflammasome is considered as a new universal therapeutic target for rheumatology and cardiology.